Deactivation and Regeneration of Sulfonated Carbon Catalysts in Hydrothermal Reaction Environments. Issue 13 (6th June 2018) - Scholz, David; Kröcher, Oliver; Vogel, Frédéric
Abstract: The deactivation pathways of sulfonated carbon catalysts prepared from different carbons were studied during the aqueous‐phase hydrolysis of cellobiose under continuous‐flow conditions. The sulfonation of carbon materials with a low degree of graphitization introduced sulfonic acid groups that are partially stable even during prolonged exposure to harsh hydrothermal treatment conditions (180 °C). The physicochemical characterization of hydrothermally treated materials coupled with the treatment of model compounds for sulfonic acids demonstrated that the stability is related to the presence of activating and deactivating substituents on the aromatic system. Besides sulfonic acid group leaching, a hitherto unknown mode of deactivation was identified that proceeds by the ion exchange of cations contained in the aqueous feed and protons of the sulfonic acid groups. Proton leaching is a fully reversible mode of deactivation by the treatment of the spent catalysts with strong Brønsted acids. Through a combined approach of physicochemical characterization, catalytic testing, and hydrothermal treatment, a methodology for the preparation of catalytically stable carbon materials that bear sulfonic acid groups was established. Abstract : Stability matters : The deactivation of sulfonated carbon catalysts in hydrothermal reaction environments occurs through the concerted effect of the sulfonic acid group and proton leaching. The stability of sulfonic acid groups is defined by the structure of the carbonaceous support. Proton leaching is a fully reversible mode of deactivation by the treatment of spent materials with stronger Brønsted acids.